2021
DOI: 10.1177/13694332211026230
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and analytical investigations on flexural behavior of bamboo beams strengthened with steel bars

Abstract: The embedding of steel bars is proposed to enhance the load-bearing performance of bamboo beams. Based on laboratory tests, the bending behavior of bamboo beams reinforced with steel bars or prestressed steel bars was analyzed using finite element software. Comparing the finite element simulation results with those measured in tests, it can be found that the load–displacement curves coincide with each other, and the strain development processes in the mid-span are basically the same. The prediction by the fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…According to the results in Table 5, a mathematical model that considers the standard value of compressive strength, the design value of compressive strength, and temperature is established, as shown in Equation (14).…”
Section: Mathematical Model Of the Design Value Of Compressive Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results in Table 5, a mathematical model that considers the standard value of compressive strength, the design value of compressive strength, and temperature is established, as shown in Equation (14).…”
Section: Mathematical Model Of the Design Value Of Compressive Strengthmentioning
confidence: 99%
“…Compared with other biomass materials, such as timber, bamboo has green, low‐carbon, energy‐saving, ecological, and environmental protection characteristics 1 and has excellent mechanical properties of fiber‐reinforced polymers 2–6 . In recent years, studies have indicated that bamboo engineering materials are suitable not only for decoration and furniture but also for building structures 7–11 and have been generally utilized in pedestrian bridges, residential buildings, and landscape buildings 12–15 . In bamboo engineering materials, reconstituted bamboo has excellent mechanical properties, 16–18 which is a research hotspot for new biomass engineering materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [ 39 ] evaluated the influence of high temperature on the physical and mechanical properties of reconstituted bamboo. Zhu et al [ 21 ] analyzed the change rule of the microstructure of reconstituted bamboo in a high‐temperature environment.…”
Section: Introductionmentioning
confidence: 99%
“…Bamboo is different from wood, [11][12][13][14] is a natural functionally graded material, [15][16][17][18] with its basic mechanical properties being related to bamboo species, structure, composition, and other factors. [19][20][21] The mechanical properties of bamboo change with age, vertical height, and the number of horizontal layers, [22,23] and the mechanical properties of its outer layer are significantly higher than those of its inner layer. [24] The strength of bamboo is related not only to its lamellar structure but also to the average bundle number [25] and the fiber volume fraction of the nodes.…”
Section: Introductionmentioning
confidence: 99%